PENERAPAN PROBLEM BASED LEARNING MELALUI MEDIA WORDWALL UNTUK MENINGKATKAN HASIL BELAJAR SISWA MATERI KEBUTUHAN MANUSIA PADA MATA PELAJARAN IPAS - Yuana Hermania Putri; Muhammad Makki; Aminudin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study uses a Problem Based Learning (PBL) learning model with wordwall media to improve student learning outcomes in science subjects. This research implements PTK (Classroom Action Research) with the implementation of 4 stages, namely planning, implementation, observation, and reflection. Techniques for collecting data include documentation, experiments, and observations. Quantitative and qualitative data analysis is applied by implementation in two cycles. At SDN 26 Cakranegara, 34 grade IV students and teachers became research subjects. The findings of this study provide complete cognitive learning outcomes that come from the pre-cycle with 15 students (45%), then the second cycle increases to 26 students (77%), and the third cycle increases to 34 students (100%). Therefore, it can be said that using the PBL learning approach with the help of Wordwall media can improve the learning outcomes of grade IV students of Science SDN 26 Cakranegara.